Reduction of healthcare access inequity using telehealth and patient travel cost subsidisation - Edwin Phillip Greenup; Daniel Best (Public Health in Practice, 2024)
Objective: Telehealth and patient travel cost subsidisation are two strategies used to reduce the effects of healthcare access inequity. Despite this shared goal, these programs are usually run independently, and their effects are infrequently compared in evaluation. Understanding how these programs are used helps ensure services are delivered efficiently. Methods: Counts of telehealth outpatient service events (TH) (n = 250171) and patient travel subsidy scheme claims (PTSS) (n = 270933) for the 2022-23 financial year were captured. Comparisons of PTSS and TH activity were made by postcode, rurality (The Accessibility/Remoteness Index of Australia (ARIA)) and health jurisdiction (Hospital and Health Service (HHS)). Results: Correlation analysis conducted on PTSS and TH activity revealed a statistically significant, moderate positive correlation (r = 0.449, p < 0.01). TH (coefficient = 0.650, p < 0.001) and rurality (coefficient = 26.208, p = 0.686) also retained their significance. Conclusions: This study established that increases in TH activity is correlated with increases in PTSS, with both programs reporting greater activity as rurality increases.